2018
DOI: 10.1007/s11207-018-1378-2
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations Accompanying a He i 10830 Å Negative Flare in a Solar Facula

Abstract: On September 21, 2012, we carried out spectral observations of a solar facula in the Si i 10827Å, He i 10830Å, and Hα spectral lines. Later, in the process of analyzing the data, we found a small-scale flare in the middle of the time series. Due to an anomalous increase in the absorption of the He i 10830Å line, we identified this flare as a negative flare.The aim of this paper is to study the influence of the negative flare on the oscillation characteristics in the facular photosphere and chromosphere.We meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Such oscillations in the solar photosphere and chromosphere are represented by five-and three-minute periods, respectively. A several-fold increase in the amplitude of these oscillations following a flare is usually clearly localized in time and space (Chelpanov and Kobanov, 2018;Farris and McAteer, 2020). This confirms the causal relationship of this phenomenon with solar flares.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Such oscillations in the solar photosphere and chromosphere are represented by five-and three-minute periods, respectively. A several-fold increase in the amplitude of these oscillations following a flare is usually clearly localized in time and space (Chelpanov and Kobanov, 2018;Farris and McAteer, 2020). This confirms the causal relationship of this phenomenon with solar flares.…”
Section: Introductionsupporting
confidence: 71%
“…Thus, we can conclude that the flare modulated the oscillation signals in the underlying atmosphere (Chelpanov and Kobanov, 2018). When the disturbance from the flare reaches the lower layers, they continue to oscillate at their typical natural frequencies, and the disturbance serves as an impetus that amplifies these natural oscillations.…”
Section: Resultsmentioning
confidence: 85%
“…It is worth noting here that not only five-and three-minute oscillations can affect the process of flare energy release, leading to QPPs, but disturbances of different layers of the solar atmosphere caused by flares can also affect the properties of these oscillations detected in various wavelength ranges (e.g. see Milligan et al, 2017;Chelpanov and Kobanov, 2018;Kobanov and Chelpanov, 2019). It is not excluded that the perturbations caused by the initial energy release of a flare can enhance these oscillations, which in turn could trigger further quasi-periodic energy releases in the flare region causing QPPs in different spectral ranges.…”
Section: Properties Of the Qpp Models And Supporting Observationsmentioning
confidence: 99%
“…The results show that the oscillation train structure of the signals resulting from an abrupt increase of the oscillation amplitudes in the lower atmosphere caused by a small-scale flare (Chelpanov and Kobanov 2018) may serve as a useful means in studies of the wave propagation processes in the transition region and corona.…”
Section: Discussionmentioning
confidence: 99%
“…In the preceding article (Chelpanov and Kobanov 2018), hereafter Article I, we analysed the influence of the small-scale flare on the oscillations in the lower atmosphere of a facula. We showed that small flare SOL2012-09-21T02:19 that we identified as a negative flare due to a sharp increase in the He i 10830 Å line absorption caused a deep modulation of the oscillation regime from the photosphere to the upper chromosphere.…”
Section: Introductionmentioning
confidence: 99%